Unsuccessful Peace-making: the Mission of Francesco da Collo and Antonio de Conti to Moscow (1518-1519) - O. F. Kudriavtsev (Vestnik MGIMO-Universiteta)
This article explores the peace mission of Francesco da Collo and Antonio de Conti, envoys of Emperor Maximilian I of the Holy Roman Empire, to Grand Prince Vasily III of Moscow in 1518–1519. The mission aimed to mediate between Moscow and the PolishLithuanian Commonwealth, seeking to align both states for a planned united Christian campaign against the Ottoman Empire, whose expansion in Southeastern Europe posed a serious threat. The study centers on da Collo’s report from the mission, which not only chronicles the negotiations but also provides rare insights into Russian diplomacy and courtly traditions of the early 16th century. The article underscores the critical role of ceremonial practices, such as receptions, banquets, and hunts, in the diplomatic culture of the period.Particular focus is given to da Collo's accounts of his interactions with Vasily III and his entourage, highlighting the crucial importance of personal meetings and informal contacts in the diplomatic process of the time. Despite the envoys' efforts, the mission achieved only a temporary one-year truce, with insurmountable barriers to a comprehensive peace including territorial disputes—especially over the control of Smolensk—and the issue of repatriating Russian prisoners of war from Poland.Furthermore, da Collo’s report serves as an early illustration of how Muscovy was constructed as an eastern, despotic power, offering one of the first examples of Russia being depicted as the “Other” in early modern European thought. The study sheds light on the complex dynamics of diplomacy in this era and reveals how these interactions contributed to the broader European perception of Russia as an alien and adversarial state.